Elevating Voices, Addressing Depression, Toxic Stress, and Equity Through Group Prenatal Care: A Pilot Study - Shannon N. Lenze; Kelly McKay-Gist; Rachel Paul; Melissa Tepe; Katherine Mathews; Sara Kornfield; Cheron Phillips; Richelle Smith; Amanda Stoermer; Ebony B. Carter (Health Equity)
Introduction: Elevating Voices, Addressing Depression, Toxic Stress and Equity (EleVATE) is a group prenatal care (GC) model designed to improve pregnancy outcomes and promote health equity for Black birthing people. This article outlines the foundational community-engaged process to develop EleVATE GC and pilot study results. Methods: We used community-based participatory research principles and the Ferguson Commission Report to guide creation of EleVATE GC. The intervention, designed by and for Black birthing people, centers trauma-informed care, antiracism, and integrates behavioral health strategies into group prenatal care to address unmet mental health needs. Using a convenience sample of patients seeking care at one of three safety-net health care sites, we compared preterm birth, small for gestational age, depression scores, and other pregnancy outcomes between patients in individual care (IC), CenteringPregnancy™ (CP), and EleVATE GC. Results: Forty-eight patients enrolled in the study (n=11 IC; n=14 CP; n=23 EleVATE GC) and 86% self-identified as Black. Patients participating in group prenatal care (EleVATE GC or CP) were significantly less likely to experience a preterm birth <34 weeks. Rates of small for gestational age, preterm birth <37 weeks, depression scores, and other pregnancy outcomes were similar across groups. Participants in CP and EleVATE GC were more likely to attend their postpartum visit and breastfeed at hospital discharge than those in IC. Discussion: Our findings model a systematic approach to design a feasible, patient-centered, community-based, trauma-informed, antiracist intervention. Further study is needed to determine whether EleVATE GC improves perinatal outcomes and promotes health equity.